(untitled) (Research, Society and Development, 2025)
Sickle cell disease is one of the most prevalent hereditary hemoglobinopathies in Brazil, showing a strong association with social determinants of health. Recent studies indicate that racial, economic, and educational inequalities directly influence the clinical course of the disease and the quality of life of patients. Social vulnerability intensifies physical and psychological suffering, interfering with treatment adherence and self-care perception. This study aims to analyze the interfaces between the epidemiological profile, social conditions, and psychological management of sickle cell disease, emphasizing the importance of integrative and humanized practices in patient care. The methodology adopts an integrative review of national and international scientific literature published between 2021 and 2025, encompassing quantitative and qualitative studies on the clinical-epidemiological and psychosocial aspects of the disease. It is expected to identify consistent correlations between social vulnerability and adverse clinical outcomes, highlighting the role of psychological support in promoting resilience and strengthening therapeutic adherence. It is concluded that the management of sickle cell disease requires an interdisciplinary and continuous approach that unites science, care, and humanization, consolidating the paradigm of comprehensive and equitable care in the context of public health.